1984
DOI: 10.1113/jphysiol.1984.sp015015
|View full text |Cite
|
Sign up to set email alerts
|

Formation of electrical coupling between embryonic Xenopus muscle cells in culture.

Abstract: SUMMARY1. Electrical coupling between embryonic Xenopus muscle cells in 1-5 day old cultures was studied after isolated cells were manipulated into contact for various periods. The coupling was examined by measuring the electrotonic spread of acetylcholine (ACh)-induced membrane depolarizations or of potential changes induced by intracellular current injection.2. In 1 day old culture, cells developed coupling rapidly after contact. Strong coupling was observed within 20 min after contact was made.3. The rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Formation of gap junctions can be induced by forcing two single cells into physical contact. In the past, this approach has been adapted to Xenopus blastulae (Loewenstein et al, 1978), Xenopus myoballs (Chow and Poo, 1984;Chow and Young, 1987) and rat cardiocytes (Rook et al, 1988). Here, we show that it is also applicable to the insect cell line C6/36.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Formation of gap junctions can be induced by forcing two single cells into physical contact. In the past, this approach has been adapted to Xenopus blastulae (Loewenstein et al, 1978), Xenopus myoballs (Chow and Poo, 1984;Chow and Young, 1987) and rat cardiocytes (Rook et al, 1988). Here, we show that it is also applicable to the insect cell line C6/36.…”
Section: Discussionmentioning
confidence: 65%
“…It consists of pushing two single cells togethr to establish a physical contact between their cell membranes and thereby allow de novo formation of gap junction channels. In othr contexts, this approach has been used before to examine Xaopus blastulae (Loewenstein et aL, 1978), embryonicXewpus muscle cells (Chow and Poo, 1984;Chow and Young, 1987), and neonatal rat heart cells (Rook et al, 1988).…”
Section: Inwrconmentioning
confidence: 99%
“…Even after the drug treatment, the hyperpolarizations produced by curarization were, in general, small-in the range of 40 PV to 1.5 mV. The cultured Xenopus embryonic muscle cells used in the present study have a high input resistance (Anderson et al, 1979;Chow and Poo, 1984), and their surface AChE has not yet achieved a high activity (Weldon et al, 1981). Both of these factors may account for the high amplitude of curare-induced hyperpolarization.…”
Section: Discussionmentioning
confidence: 80%
“…The average peak amplitude and frequency of these MEPPs were 2.2 + 0.3 mV and 1.3 + 0.5 (n = 7 cells; +SEM), values close to those previously reported in similar Xenopus culture systems (Kidokoro et al, 1980). These MEPPs are much larger than that of the mature neuromuscular junction, presumbly due to the fact that these muscle cells have relatively high input resistance (50 to 100 megohms; Chow and Poo, 1984; see also Anderson et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…The developmental significance of this early ACh secretion is now beginning to be understood. Because of the high input resistance of the embryonic muscle cell (Chow and Poo, 1984) spontaneous ACh secretion at developing synapses produces large postsynaptic potentials, many of which are capable of inducing action potentials and contraction of the muscle cell (Xie and Poo, 1986). It has been shown that the differentiation of muscle striations in Xenopus myocytes is regulated by the ACh-induced contraction during the first few days of synaptogenesis (Kidokoro and Saito, 1988).…”
Section: Discussionmentioning
confidence: 99%